O teatro-fórum na busca de temas geradores: uma proposta de ensino na educação de jovens e adultos (EJA) - Lima, Maria Tânia Gomes (2023)
There are countless challenges found in education, mainly regarding Youth and Adult Education (EJA), where low performance and high school dropouts predominate. In this context, teachers face the challenge of building practices that provide students with greater involvement with the discipline and, at the same time, a more critical view of reality. The purpose of this work is in line with the pedagogy of Paulo Freire (2009), which contributes in an innovative way by bringing the generative themes as a method of disalienation and learning to education. Still, this research is in accordance with the proposal of Augusto Boal (2005), which is based on the liberating transforming social character and presents the methodology of the “Theatre of the Oppressed”, which develops a scenic pedagogical method. The two works present an ethical-political positioning of social transformation, through the bias of education and culture. Thus, it is considered relevant to carry out a study that highlights the similarities between these two fields of action, seeking the generating themes through Forum Theater. The objective of the research was to develop a proposal for the teaching of EJA through the Teatro-forum of Augusto Boal (2005) in order to extract the generating theme of Paulo Freire (2009). In this work, some of the aspects about how the Theater-forum helps in the definition of the generating theme were addressed, in addition to opening possibilities to build a vision of the school reality, to understand the personal side of each student, and the context in which he is inserted, with the purpose of finding viable solutions for better learning and better school performance. The project took place in five moments: the first was a conversation circle; the second, the application of a socioeconomic questionnaire; the third, suggestions of themes for the script of the play; the fourth, the execution of the play by Teatro-forum, which was recorded on video; the fifth, a conversation wheel to critically analyze the extraction of the generating theme. The video of the play, together with an instructional guide, is the educational product of the work, which is entitled: Teatro Forum: Script for a proposal in the Education of Young People and Adults. The result associated Teatro Fórum in the definition of the generating theme, extracted from the student community in question, with the aim of promoting a more meaningful and relevant teaching for students.